Purification of retinal ganglion cells using low-pressure flow cytometry - Kiran J. Mcloughlin; Kiran J. Mcloughlin; Afnan M. Aladdad; Afnan M. Aladdad; Andrew J. Payne; Andrew J. Payne; Anna I. Boda; Anna I. Boda; Sayra Nieto-Gomez; Sayra Nieto-Gomez; Karl E. Kador; Karl E. Kador (Frontiers in Molecular Neuroscience, 2023)
Purified Retinal Ganglion Cells (RGCs) for in vitro study have been a valuable tool in the study of neural regeneration and in the development of therapies to treat glaucoma. Traditionally, RGCs have been isolated from early postnatal rats and mice, and more recently from human in vitro derived retinal organoids using a two-step immunopanning technique based upon the expression of Thy-1. This technique, however, limits the time periods from which RGCs can be isolated, missing the earliest born RGCs at which time the greatest stage of axon growth occurs, as well as being limited in its use with models of retinal degeneration as Thy-1 is downregulated following injury. While fluorescence associated cell sorting (FACS) in combination with new optogenetically labeled RGCs would be able to overcome this limitation, the use of traditional FACS sorters has been limited to genomic and proteomic studies, as RGCs have little to no survival post-sorting. Here we describe a new method for RGC isolation utilizing a combined immunopanning-fluorescence associated cell sorting (IP-FACS) protocol that initially depletes macrophages and photoreceptors, using immunopanning to enrich for RGCs before using low-pressure FACS to isolate these cells. We demonstrate that RGCs isolated via IP-FACS when compared to RGCs isolated via immunopanning at the same age have similar purity as measured by antibody staining and qRT-PCR; survival as measured by live dead staining; neurite outgrowth; and electrophysiological properties as measured by calcium release response to glutamate. Finally, we demonstrate the ability to isolate RGCs from early embryonic mice prior to the expression of Thy-1 using Brn3b-eGFP optogenetically labeled cells. This method provides a new approach for the isolation of RGCs for the study of early developed RGCs, the study of RGC subtypes and the isolation of RGCs for cell transplantation studies.